2021
DOI: 10.3390/healthcare9111541
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices Regarding Brucellosis among Parents in Aseer Region, Southwestern Saudi Arabia

Abstract: This study aimed to investigate the knowledge, attitudes, and practices regarding brucellosis among parents in the Aseer region of southwestern Saudi Arabia in order to estimate the population sectors that are at high risk for accidental exposure to brucellosis. This was a cross-sectional survey conducted in 2018, including 311 participants representing various genders, ages, and levels of education. Bivariate analysis showed a significant association of good awareness of the disease with the male gender and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 30 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…A positive attitude toward the importance of chronic disease in cattle and especially abortion lead to better identification of disease in livestock 3 , 4 . It was evidenced that raising the brucellosis-correct information is the main aspect that has influenced their willingness and ability to modify risky behaviors of brucellosis 3 , 4 , 6 , 17 . Therefore, it is critical for the relevant healthcare professionals and authorities to take note of positive attitude as the main influential factors to modify risky behaviors of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A positive attitude toward the importance of chronic disease in cattle and especially abortion lead to better identification of disease in livestock 3 , 4 . It was evidenced that raising the brucellosis-correct information is the main aspect that has influenced their willingness and ability to modify risky behaviors of brucellosis 3 , 4 , 6 , 17 . Therefore, it is critical for the relevant healthcare professionals and authorities to take note of positive attitude as the main influential factors to modify risky behaviors of brucellosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of brucellosis, high-risk behaviors, including inappropriate behaviors such as consumption of unpasteurized dairy products, lack of personal protective equipment such as masks and gloves when working in the barn and warehouse, and contact with livestock secretions of infected animals, which are completely related to insufficient knowledge and awareness of people, their self-efficacy status and attitude 9 , 12 . Preventing high-risk behavior depends on increasing the level of awareness and improving the level of attitudes and beliefs, and a prerequisite for disease prevention is to have self-efficacy or the belief of people in their abilities to control risky behavior 4 , 6 , 14 , 16 . Since most livestock are kept mobile and there is no individual identification system, the eradication, and control of this infection may not be achieved by and test, slaughter, and vaccination only.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying disease prevention benefits can prepare the ground for further steps toward disease prevention. [ 37 ] After the HEI implementation, the score was improved among the subjects in the present study.…”
Section: Discussionmentioning
confidence: 61%
“…The studies conducted in Kolkata in India, Tanzania, Iran, and China reported that increased awareness and sensitivity ultimately lead to self-care to prevent any disease. [ 35 36 37 40 ] Finally, preventive behaviors against brucellosis can be encouraged by using the HEI paradigms. [ 41 42 ]…”
Section: Discussionmentioning
confidence: 99%